PENGARUH INTENSITAS PENGGUNAAN SMARTPHONE TERHADAP PRESTASI BELAJAR MAHASISWA DI PERGURUAN TINGGI - Ratu, Andrew Daniel; Sujana , I Putu Windu Mertha; Asri Sidaryanti, Ni Nyoman (Ganesha Civic Education Journal, 2026)
The development of information and communication technology has brought significant changes to society, particularly among university students as active smartphone users. This study aims to analyze the effect of smartphone usage intensity on students’ academic achievement in higher education. The research employed a quantitative method using a survey approach through the distribution of questionnaires to 94 student respondents. The data were analyzed to determine the relationship between the frequency of smartphone use and students’ academic performance. The findings indicate that smartphone usage has both positive and negative impacts. On the positive side, smartphones facilitate students in accessing learning resources, scientific journals, online learning media, and academic communication with lecturers and fellow students. This contributes to improving the effectiveness of the learning process. However, excessive use for non-academic activities such as social media, entertainment, and digital games has the potential to cause academic procrastination, reduce sleep quality, and disrupt learning concentration. Nevertheless, the results show that most students are still able to maintain good academic performance, as reflected in stable GPA achievement. Therefore, the impact of smartphone use on academic achievement largely depends on usage patterns, self-control, and students’ ability to utilize technology productively.